Hygiene and health at work - Vocam Worldwide Publishing ([Orlando, Fla.] : Vocam Worldwide Publishing, [1997], 1997)
Explains the types of illnesses and infections common at home and at work, and looks at how germs are spread and how to improve workplace hygiene. Also shows how to keep fit and healthy to prevent the spread of illness and disease
VCD format
Keywords: Health self-care; Industrial hygiene; Hygiene; Health